Effect of Dietary Fat Supplementation during Late Pregnancy and First Six Months of Lactation on Maternal and Infant Vitamin A Status in Rural Bangladesh - Alam, Dewan S; van Raaij, Joop MA; Hautvast, Joseph GAJ; Yunus, M; Wahed, MA; Fuchs, GJ (Journal of Health, Population and Nutrition, 2010)
Dietary fat intake is extremely low in most communities with vitamin A deficiency. However, its role in vitamin A status of pregnant and lactating women is poorly understood. The aim of the study was to examine the effect of supplementing women with fat from mid-/late pregnancy until six months postpartum on their vitamin A status and that of their infants. Women recruited at 5-7 months of gestation were supplemented daily with 20 mL of soybean-oil (n=248) until six months postpartum or received no supplement (n=251). Dietary fat intake was assessed by 24-hour dietary recall at enrollment and at 1, 3 and 6 months postpartum. Concentrations of maternal plasma retinol, β-carotene, and lutein were measured at enrollment and at 1, 3 and 6 months postpartum, and those of infants at six months postpartum. Concentration of breastmilk retinol was measured at 1, 3 and 6 months postpartum. The change in concentration of plasma retinol at three months postpartum compared to pregnancy was significantly higher in the supplemented compared to the control women (+0.04 vs -0.07 μmol/L respectively; p<0.05). Concentrations of plasma β-carotene and lutein declined in both the groups during the postpartum period but the decline was significantly less in the supplemented than in the control women at one month (β-carotene -0.07 vs -0.13 μmol/L, p<0.05); lutein -0.26 vs -0.49 μmol/L, p<0.05) and three months (β-carotene -0.04 vs -0.08 μmol/L, p<0.05; lutein -0.31 vs -0.47 μmol/L, p<0.05). Concentration of breastmilk retinol was also significantly greater in the supplemented group at three months postpartum than in the controls (0.68±0.35 vs 0.55±0.34 μmol/L respectively, p<0.03). Concentrations of infants' plasma retinol, β-carotene, and lutein, measured at six months of age, did not differ between the groups. Fat supplementation during pregnancy and lactation in women with a very low intake of dietary fat has beneficial effects on maternal postpartum vitamin A status. Key words: Community-based studies; Fat supplementation; Infant; Postpartum;Pregnancy; Vitamin A; Vitamin A deficiency; Bangladesh DOI: 10.3329/jhpn.v28i4.6039 J HEALTH POPUL NUTR 2010 Aug;28(4):333-342